Neuroleptic Malignant Syndrome: A Case Aimed at Raising Clinical Awareness - Jad Al Danaf; John Madara; Caitlin Dietsche (Case Reports in Medicine)
A 60-year-old man with a history of bipolar disorder on risperidone, bupropion, and escitalopram was admitted for community acquired streptococcal pneumonia. Four days later, he developed persistent hyperthermia, dysautonomia, rigidity, hyporeflexia, and marked elevation of serum creatine phosphokinase. He was diagnosed with neuroleptic malignant syndrome (NMS) and improved with dantrolene, bromocriptine, and supportive therapy. This case emphasizes the importance of considering a broad differential diagnosis for fever in the ICU, carefully reviewing the medication list for all patients, and considering NMS in patients with fever and rigidity.